Elevated risk of squamous-cell carcinoma of the lung in heavy smokers carrying the variant alleles of the TP53 Arg72Pro and p21 Ser31Arg polymorphisms - Popanda, Odilia; Edler, Lutz; Waas, Peter; Schattenberg, Torsten; Butkiewicz, Dorota; Muley, Thomas; Dienemann, Hendrik; Risch, Angela; Bartsch, Helmut; Schmezer, Peter (Lung cancer, 2007)
Alterations in cell cycle regulation and apoptosis leading to malignant transformation could be caused by common genetic variants in tumor suppressor genes. The effects of the TP53 polymorphism Arg72Pro on lung cancer risk have been investigated in numerous studies with, however, conflicting results. In many studies, important risk modifiers such as smoking or tumor histology were not taken into account. We therefore investigated the combined effects of polymorphisms in TP53 (Arg72Pro) and p21/CDKN1A (Ser31Arg) and smoking on lung cancer risk. Our case-control study consisted of 405 patients with lung cancer, mainly squamous-cell carcinoma (185) and adenocarcinoma (177) and 404 unmatched tumor-free hospital controls. Multivariate regression analysis showed a moderate but statistically significant risk of lung cancer overall and especially of squamous-cell carcinoma (OR, 1.65; CI, 1.10-2.47) for TP53 72Pro allele carriers. The risk was markedly increased in heavy smokers (>20 pack-years) with squamous-cell carcinoma (OR, 2.80 in patients homozygous for 72Pro; CI, 1.19-6.58), but not in light smokers (≤20 pack-years). The results for the p21 Ser31Arg polymorphism suggested that 31Ser is a moderate-risk allele for squamous-cell carcinoma. Analysis of the combined effects of the two polymorphisms revealed a higher OR for TP53 72Pro carriers homozygous for p21 31Ser than for 72Pro carriers in general; this effect being most pronounced in heavy smokers with squamous-cell carcinoma (OR, 3.84; CI, 1.46-10.1). Our data indicate that the TP53 Arg72Pro polymorphism increases the risk for squamous-cell carcinoma mainly in heavy smokers. The observed interaction with smoking is biologically plausible as, for the 72Pro p53 variant, decreased apoptosis and extended G1 cell cycle arrest is reported after carcinogen exposure. Nevertheless, confirmation by further molecular and epidemiological studies is warranted.